School counselors as practitioners : building on theory, standards, and experience for optimal performance - Nelson, Judy A.; Wines, Lisa A. (New York, NY : Routledge, 2024)
"School Counselors as Practitioners, Second Edition is a hands-on, practice-based, task-oriented guide to being an effective school counselor. Thoroughly revised, this textbook continues to address the foundation of school counseling, the main duties of a school counselor, the skills needed to be successful, and what to expect as a school counseling professional. All these topics have been updated to include the current thinking, research and evidence-based practices, and challenges in school counseling. Additionally, interviews of principals, school counselors, and community leaders are included, which provide readers with the reality of how to navigate the waters of the comprehensive school counseling program. The chapter authors also highlight the necessity of designing, implementing, and evaluating the counseling program for continuous improvement. Online resources provide students with templates and handouts for on-the-job responsibilities, as well as quiz questions for every chapter. This updated edition is essential reading for counselor educators, graduate students enrolled in a school counseling program, supervisors of school counselors, including administrators, and practicing school counselors"--
Becoming a school counselor / Frannie Neal, Judy A. Nelson -- Satisfying and challenging experiences of school counselors / Judy A. Nelson -- Social trends affecting the school counseling profession / Judy A. Nelson -- Defining the professional and student standards of your program / Judy A. Nelson -- School counseling as a responsive service / Kim McGough, Robika Mylroie -- Crisis management and trauma-informed school counseling / Kathy McDonald, Erica Fenderson -- Program planning and program focus / Jennifer Akins -- Managing the comprehensive school counseling program and non-counseling duties / Carleton Brown -- Managing the goals of the program with post-secondary opportunities / Lia Falco, Sam Steen -- Managing the technology needs of the school counseling program / Shannon McFarlin, Rachael Whitaker -- Instruction through counseling curriculum / Helena Stevens -- Appraisal and advisement / Tim Brown, Glenda Johnson -- Counseling individuals / Kathy McDonald, Laura Hodges -- Counseling small groups / Judy A. Nelson, Benny Malone -- Collaboration, consultation, and appropriate referrals / Le'Ann Solmonson -- Assessing school-wide cultural competence / Rebecca Bustamante, Judy A. Nelson -- Assessment, data collection, and results reporting in school counseling / Tiffany Simon, Ernest Cox, Ashley Baines -- The evaluation process : annually assessing school counselor performance and competency, along with a conducting comprehensive school counseling program evaluation (audit) : a special briefing / Lisa A. Wines -- School counselor leaders / Lisa A. Wines, Natalie Fikac -- Supervision, mentoring, and professional development / Lisa A. Wines, Judy A. Nelson -- Professional ethics and the law / Teri Sartor, Judy A. Nelson, Lisa A. Wines -- Counseling with common-sense / Lisa A. Wines, Franklin Sampson.
Keywords: Student counselors -- Training of; Educational counseling; EDUCATION / Counseling / General; PSYCHOLOGY / Psychotherapy / Counseling